Performance of uPVC RC-filled Pipe Columns exposed to Thermal Cyclic Loading - Musonda, Joshua; Mwero, John Nyiro; Abongo, Kepha (Engineering, Technology & Applied Science Research, 2025)
This study analyzes the performance of unplasticized Polyvinyl Chloride (uPVC) RC-filled pipe columns when exposed to thermal cyclic loading. The exposure simulates hot environments with a peak temperature of 60 °C for 28, 56, and 112 days of Heating-Cooling Cycles (HCC). The experimental analysis focuses on uPVC residual strength after thermal cyclic loading and load-carrying capacity, ductility, and stress-strain behavior of uPVC RC-filled pipe columns. Tensile tests of extracted uPVC specimens after exposure demonstrated no change in ultimate tensile strength but a progressive decline in elastic modulus, reducing by 17.24% and 24.56% after 28 and 56 cycles, respectively. The uPVC confined exposed samples exhibited an initial increase in load-carrying capacity by a factor of 1.39 compared to the unexposed unconfined samples at ambient temperature. However, this increase was followed by a gradual decline to 1.32 and 1.26 at 56 and 112 cycles, respectively. Despite this, the load-bearing capacity of the confined samples was still higher than that of the unexposed, confined samples. Thermal cycling significantly reduced maximum lateral and axial strain at failure by up to 85% at 112-HCC, with ductility declining by 50.9% at 28 cycles and continuing to decrease gradually at higher cycles. Failure modes shifted from ductile in confined unexposed samples to brittle and explosive in thermally cycled samples, highlighting reduced confinement effectiveness. Predictive models demonstrated a high degree of accuracy in estimating peak strength and strain, with average absolute errors of 0.16% and 7.65%, respectively. Long-term projections suggest that confinement effectiveness could decrease to 1.06, which is the ratio of confined exposed strength (fccx) to unconfined unexposed strength (fco) after 50 years of thermal exposure, emphasizing the necessity for enhanced design guidelines to optimize the performance of uPVC-confined RC columns in fluctuating temperature environments, particularly in consideration of thermal cyclic loading.